The Significance of 18F-Fluorocholine-PET/CT as Localizing Imaging Technique in Patients with Primary Hyperparathyroidism and Negative Conventional Imaging - Fischli, Stefan; Suter-Widmer, Isabelle; Nguyen, Ba Tung; Müller, Werner; Metzger, Jürg; Strobel, Klaus; Grünig, Hannes; Henzen, Christoph (Frontiers in Endocrinology, 2018)
Objective: The essential prerequisite for focused parathyroidectomy in patients with primary hyperparathyroidism (pHPT) is proper localization of all autonomic tissue. Sensitivity of conventional imaging modalities (ultrasound, 99mTc-sestamibi scintigraphy/SPECT/CT) is influenced by different factors (i.e. size/weight and position of autonomic tissue) and decreases in the presence of a multinodular goiter. Therefore, a considerable percentage of pHPT patients have negative or equivocal localization studies before surgery. The aim of our study was to evaluate the utility of FCH-PET/CT for preoperative localization in patients with pHPT and negative/equivocal 99mTc-sestamibi scintigraphy/SPECT/CT and/or ultrasound. Methods and Measurements: Between 2014-2017 a total of 39 patients with pHPT and negative/equivocal conventional imaging were referred for FCH-PET/CT. In the analysis, we included those (n=23) who had surgery and a histopathologic workup of the lesions. Results: 19/23 patients demonstrated no tracer uptake with 99mTc-sestamibi scintigraphy/SPECT/CT, 6 patients had an equivocal sonographic lesion, multinodular goiter was present in 43% (10/23). In 21/23 patients with hyperfunctioning parathyroid tissue was identified correctly by FCH-PET/CT (21 true-positive, 1 false-negative, 1 false-positive; per-patient sensitivity 95.5% [95%-CI 77.2-99.9]). 29 lesions were resected (21 true positives, 3 false negatives, 1 false positive, and 4 true negatives; per-lesion sensitivity 87.5% [95% CI, 67.6-97.3]). All patients were classified as having surgical success according to a decrease of intraoperative PTH of ≥50% and normalization of postoperative serum calcium levels. Conclusion: Despite a high prevalence of multinodular goiter, diagnostic accuracy of FCH-PET/CT in our patient group was excellent. Therefore, FCH-PET/CT is a promising new imaging tool in patients with pHPT and negative/equivocal results by conventional imaging techniques.